Native European eels as a potential biological control for invasive crayfish. (14th November 2014) - Musseau, Camille; Boulenger, Clarisse; Crivelli, Alain J; Lebel, Isabelle; Pascal, Marine; Boulêtreau, Stéphanie; Santoul, Frédéric
Summary Invasive species may have strong negative impacts on ecosystems. Invasive crayfish are well known to cause ecological imbalances in freshwater systems and have become targets in eradication programmes. The red swamp crayfish (Procambarus clarkii) is vulnerable to predation by several fish species. The European eel (Anguilla anguilla) appears to be a very good candidate given its benthic feeding activity and ability to recognise prey by odour. Our study took place from 2009 to 2013 in a closed system in south‐eastern France in which ponds were sampled twice a year by passive capture methods to evaluate trends in populations of potential prey. Eel population dynamics were assessed by means of a multistate capture–recapture model, and diet assessment was performed using stable isotope analysis in October 2010 and October 2012. Our results show that the invasive crayfish was the most important prey in the eel diet, and every size‐class of crayfish was preyed upon by the predator. A high predator density, approaching carrying capacity for the European eel in this system, strongly affects P. clarkii populations, leading them to their collapse, but not eradication.